Winter in Tuscany : cozy recipes and the quanto basta way - Guinness, Amber (Thames & Hudson Inc., 2025)
"Winter in Tuscany celebrates the region's rich culinary and cultural traditions with a quanto basta approach -- the intuitive, Italian method of 'just enough' -- and brings the heart of Tuscany's cozy autumnal and wintry flavors to your kitchen. But quanto basta is more than just a philosophy for cooking; it's a metaphor for life. This book celebrates life in the offseason; an ode to exploring Tuscany's villages and countryside when the crowds have thinned, allowing for a deeper, more intimate connection with the culture, food, and landscapes. Filled with an array of hyperlocal, traditional recipes for the home cook, Winter in Tuscany is an invitation to slow down and appreciate the beauty in small moments and big flavors."--Publisher description.